Identification of Allergenic Tropomyosins with Known and Unknown Sequences in Seafood Products - Marta Godlewska; Piotr Minkiewicz; Małgorzata Darewicz; Anna Iwaniak (Applied Sciences)
Invertebrate tropomyosins belong to the key food allergens. Several peptides likely to be released during proteolysis can be found in many sequences of proteins from this family. The aim of the present study was to evaluate the possibility of identifying tropomyosins with known and unknown amino acid sequences in unheated, boiled and fried seafoods. The workflow included in silico proteolysis simulation of tropomyosin sequences and analysis of the distribution of resulting peptides among proteins. The experiment entailed the proteolysis of unheated, boiled and fried products, containing crustaceans or mollusks, and the identification of resulting peptides using LC-MS/MS. Finally, taxonomic lineages of identified peptides were determined. Predicted peptides were identified in unheated samples. The boiling of seafoods resulted in an increase in the length of peptides containing predicted sequences. Some peptides from the boiled samples contained entire linear epitopes. The prediction of tropomyosin cleavage sites failed in the case of fried products. Peptides from the unheated and boiled samples were attributed to crustacean, arthropod or molluscan tropomyosins. In turn, peptides from the fried samples possessed inconclusive taxonomic lineages. Our results show that bioinformatics analysis (especially using Unipept program) may be a viable tool supporting LC-MS/MS experiments aimed at the detection of allergens.